Used High Collimation UV-LEDs With a Miniaturized Optomechanical Device for the Detection of Direct Bilirubin - Zhi Ting Ye; Shen Fu Tseng; Jun Yi Wu; Hsin Ching Kuo (IEEE Photonics Journal)
Invasive blood testing is the most used method for testing bilirubin levels. However, invasive blood testing must be carried out by professionally trained medical staff to avoid the risk of infection. Apart from being present in blood, direct bilirubin is excreted in human urine. Therefore, this study proposed a non-invasive method, using high collimation ultraviolet-light-emitting diodes (HC UV-LEDs) as the light source to design a miniaturized optomechanical device (MOD) for direct bilirubin detection in urine. The designed MOD was used to analyze different concentrations of direct bilirubin using its absorbance spectrum to achieve a non-invasive detection method. The HC UV-LEDs MOD proposed in this study offers the benefits of being non-invasive and providing a quantitative analysis of direct bilirubin.